ALTERNATIVE CONTROL OF INSECT PESTS IN VEGETABLE PLANTS USING LOCAL WISDOM APPROACH - Lukmanul Hakim; Abdul Muis (SCAD Independent, 2016)
This research aimed to determine the local wisdom of the community of Lembah Seulawah Sub-district, Aceh Besar, Indonesia of controlling insect pests in vegetable plants. In addition, the study intended to examine the impact of using paper as a mechanical trap for insect pests in vegetable plants. Both qualitative and quantitative methods were used in this research. The qualitative data were obtained through interviews with farmers, whereas the quantitative data were collected from an experiment. Thirty randomly-selected respondents were interviewed and then the qualitative and quantitative data processing was performed. The results showed that they still use plant-based materials as insecticides which constitute the local wisdom of controlling insect pests in vegetable plants. The plants used as insecticides were, among others, garlic (Allium satifum), castor bean seeds (Ricinus communis), lemongrass, neem seeds, and thorny amaranth as the trap plants.